Efforts to Realize National Standard School Administration at SMKS Bina Insani Malunda, Majene - Elviana, Elviana; Arhas, Sitti Hardiyanti; Isgunandar, Isgunandar (Journal of Public Policy and Local Government (JPPLG), 2025)
School administrative  is a series of processes, policies, and practices that are implemented to manage school activities effectively and efficiently. The goal is to ensure that all administrative activities support the achievement of educational goals, in accordance with the established standards. The main purpose of this study is to find out the efforts to realize national standard school administrative governance and to find out the supporting and inhibiting factors in efforts to realize national standard school administrative governance at SMKS Bina Insani Malunda Majene Regency. This research is qualitative descriptive research. This research focuses on efforts to realize national standard school administrative governance based on planning, organizing, implementing, and supervising indicators. To achieve the research objectives, data collection techniques were used, namely observation, interviews, and documentation. Based on the results of the study, it shows that efforts to realize national standard school administrative governance at SMKS Bina Insani Malunda Majene Regency can be seen from the indicators of planning, organizing, implementing, and supervising in the "quite good" category. This is seen from the planning aspect, which holds a plan preparation meeting with the participation of all school personnel to set clear and directed goals. Organizing by dividing tasks according to the ability of staff, even though the limited number of staff causes some staff to have double tasks, can still optimize performance and achieve set goals. The implementation of tasks is emphasized on seriousness and thoroughness in carrying out the predetermined plan, with each administrative staff playing an important role in completing the task according to the plan. Supervision, which is carried out periodically and collaboratively to monitor staff performance and identify obstacles that may arise. These measures demonstrate a strong commitment to improving the governance of school administration towards the desired national standards. Supporting factors include existing facilities and infrastructure, good cooperation, and the leadership of the principal. Inhibiting factors include lack of facilities and infrastructure, limited staff, and high workload.